Actitudes lingüísticas en tres comunidades hispano-lusas de fronteira: Miranda do Douro, Val do Ellas e Olivença - Xosé-Henrique Costas (Lengas)
On the border between Spain and Portugal there are some enclaves that resist linguistic and cultural assimilation under the pressure / oppression of the corresponding state linguistic ideology, Portuguese or Spanish.This is Miranda do Douro (Tras-os-Montes, Portugal) where there is still a community of 3.500 people speaking a variety of Asturian-Leonese Language called Mirandes; of the Val do Río Ellas, or Xálima (northwest of Cáceres, Spain), where there is a community of 4.500 speakers of varieties derived from medieval Galician; and from Olivenza (Badajoz, Spain) where still 3.000 people keep the Portuguese language alive. Between March 2020 and November 2022 we conducted more than 550 surveys of language uses and attitudes of speakers of these varieties. The historical, cultural, sociolinguistics and legislative starting points were different in, but the results are very similar in two (Miranda and Olivenza) and very special in the other (Val do Ellas). We will try to take a sociolinguistic approach to the attitudes and linguistic ideologies of these minorized varieties.